2015
DOI: 10.1016/j.drugalcdep.2014.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive manifestations of drinking–smoking associations: Preliminary findings with a cross-primed Stroop task

Abstract: Background Despite tremendous growth in research examining the role of cognitive bias in addictive behaviors, scant consideration has been paid to the close association between smoking and drinking behavior. This study sought to determine whether an association between smoking and drinking could be observed at an implicit level using a novel cognitive bias task, as well as characterize the relationship between performance on this task and clinically relevant variables (i.e., heaviness of use/dependence). Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 72 publications
(74 reference statements)
1
10
0
Order By: Relevance
“…Taken together, these findings extend prior research showing that heavier drinking is a risk factor for both smoking and relapse back to smoking relapse (Kahler et al, 2010; Koçak et al, 2015; Leeman et al, 2008; McClure, Wetter, de Moor, Cinciripini, & Gritz, 2002). Findings are also consistent with recent evidence that implicit smoking-drinking associations are strongest among heavier drinkers (Oliver & Drobes, 2015). This result suggests a tendency for smokers with proclivity toward heavy alcohol use and alcohol-related problems to seek alcohol preferentially in the context of cigarette deprivation, and a possible cognitive mechanism linking smoking (or lack thereof) and heavier drinking behavior together.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Taken together, these findings extend prior research showing that heavier drinking is a risk factor for both smoking and relapse back to smoking relapse (Kahler et al, 2010; Koçak et al, 2015; Leeman et al, 2008; McClure, Wetter, de Moor, Cinciripini, & Gritz, 2002). Findings are also consistent with recent evidence that implicit smoking-drinking associations are strongest among heavier drinkers (Oliver & Drobes, 2015). This result suggests a tendency for smokers with proclivity toward heavy alcohol use and alcohol-related problems to seek alcohol preferentially in the context of cigarette deprivation, and a possible cognitive mechanism linking smoking (or lack thereof) and heavier drinking behavior together.…”
Section: Discussionsupporting
confidence: 90%
“…However, this finding is not unlike those reported in previous studies. Oliver and Drobes (2015) found that the association between implicit smoking and drinking cognitions was strongest among respondents with greater levels of alcohol use and dependence. Ostafin and Palfai (2006) also found that binge drinking, but not alcohol frequency, quantity, or consequences of use were correlated with alcohol-approach IAT scores in 88 hazardous drinking college students (score of 8 or higher on the AUDIT).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a modified Drug Stroop task, response time to smoking words was slower following alcohol priming words relative to neutral words. 42 In future studies, cigarette AB should be assessed independently of cocaine AB. A larger sample size would facilitate further analysis of individual differences and enable broader conclusions to be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the sight of cigarettes and an ashtray may provoke craving for alcohol, and the smell of an alcoholic beverage may increase the urge to smoke. Indeed, cross-cue reactivity (alcohol and smoking picture primes) has demonstrated delayed response latencies to both alcohol- and smoking-related words (21). It is established that cue-induced alcohol craving or craving to smoke may provoke increased drug use and promote relapse to drinking or smoking.…”
Section: Craving In the Human Laboratorymentioning
confidence: 99%